2008
DOI: 10.1021/ie800320d
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Lignin Structural Features on Eucalyptus globulus Kraft Pulping

Abstract: Clones of Eucalyptus globulus Labill. (5- to 7-year-old), from a common geographic area, were evaluated for chemical pulping easiness. Significant variations were observed in the pulp yield and specific wood consumption to produce pulps with similar kappa numbers, as well as in the strength properties of the resulting kraft pulps. Comprehensive lignin analyses were undertaken in an attempt to rationalize the observed differences in these clones’ pulping performance. While lignin content did not correlate with … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

14
24
0
3

Year Published

2010
2010
2018
2018

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 37 publications
(41 citation statements)
references
References 31 publications
(105 reference statements)
14
24
0
3
Order By: Relevance
“…No statistical difference was found for the amount of guaiacyl units, with similar values found in both tension and opposite wood (350-400 µmoles/g lignin). Similar trends were previously reported for tension wood of other species where low lignin content correlated with high syringyl units (Joseleau et al 2004, Pilate et al 2004, Guerra et al 2008. Ralph et al (2004) and Guerra et al (2008) previously reported a large amount of S units favours the generation of uncondensed aril-ether linkages (high amount of S units and low lignin content also correlated well with high frequency of β-O-4 linkages) which was also observed for the tension wood (46% β-O-4) in comparison with the opposite wood (39% β-O-4).…”
Section: Chemical Characterization Of Tension and Opposite Wood Of Esupporting
confidence: 88%
“…No statistical difference was found for the amount of guaiacyl units, with similar values found in both tension and opposite wood (350-400 µmoles/g lignin). Similar trends were previously reported for tension wood of other species where low lignin content correlated with high syringyl units (Joseleau et al 2004, Pilate et al 2004, Guerra et al 2008. Ralph et al (2004) and Guerra et al (2008) previously reported a large amount of S units favours the generation of uncondensed aril-ether linkages (high amount of S units and low lignin content also correlated well with high frequency of β-O-4 linkages) which was also observed for the tension wood (46% β-O-4) in comparison with the opposite wood (39% β-O-4).…”
Section: Chemical Characterization Of Tension and Opposite Wood Of Esupporting
confidence: 88%
“…Similar results were also reported for various clones of E. grandis and the hybrid of E. grandis × E. urophylla (Gomide et al 2005;Guerra et al 2009). The correlation was not as strong, leading to the suggestion that other lignin structural features, in addition to the S/G ratio, may also play a role (Guerra et al 2009). …”
Section: Impact Of Syringyl-to-guaiacyl Ratio Of Lignin On Biomass Cosupporting
confidence: 86%
“…Even within the same species of E. globulus wood, evidence of the influence of S/G ratio on pulp yield and ease of pulping has been reported, leading to the inclusion of lignin S/G ratio as a selection parameter in clonal breeding programs for pulpwood production (González-Vila et al 1999;del Río et al 2005). Similar results were also reported for various clones of E. grandis and the hybrid of E. grandis × E. urophylla (Gomide et al 2005;Guerra et al 2009). The correlation was not as strong, leading to the suggestion that other lignin structural features, in addition to the S/G ratio, may also play a role (Guerra et al 2009).…”
Section: Impact Of Syringyl-to-guaiacyl Ratio Of Lignin On Biomass Cosupporting
confidence: 54%
See 1 more Smart Citation
“…Therefore, B. spiciformis should show a better performance during alkaline pulping procedures due to its lowest lignin content and highest S-type units amount than P. angolensis, in addition to its higher cellulose and alpha-cellulose content. In hardwoods with high pulpability, as E. globulus genotypes, the S/G ratio reported is higher (between 2,0-5,5) while lignin and cellulose contents are in agreement with these values (Guerra et al 2008, Aguayo et al 2015.…”
Section: Chemical Composition Of Woodsupporting
confidence: 62%